(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
Psychology has, essentially, benefited people because it can explain why people behave the way they do. A psychologist with this level of professional insight can help people improve their decision-making, stress management, and behavior by understanding past behavior to better predict future behavior. All of this can lead to a more successful career, better relationships, increased self-confidence, and overall improved communication. Psychology’s scope was once limited to people’s mental health. Psychology is used to help mentally stressed people who had been through traumatic experiences. Present research is based upon a survey for the impact of motivation and job satisfaction upon the organization commitment and performance of teachers in private school.